2018
DOI: 10.1111/pbr.12621
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the protein and fat contents of peanut (Arachis hypogaea L.) cultivars released in China in the last 60 years

Abstract: Peanut is an important oil and cash crop in China. We selected 540 peanut cultivars—released in three ecological regions of China (Yellow River, Yangtze River and Southeast Coast regions)—to examine changes in quality characters and pod yield in the last 60 years. From 1957 to 2016, crude fat, protein and pod yields in peanut cultivars increased significantly in the three regions. In contrast, the crude fat content, as opposed to its yield, did not change in the Yellow River region, increased in the Yangtze Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
1
5
1
Order By: Relevance
“…Based on the violin plot, most fat and protein contents of peanut varieties ranged from 49− 54 g/ 100 g and 22− 27 g/100 g, respectively. This is similar compared with previous studies for fat (48− 55 g/100 g) (Li et al, 2018) and protein (20− 26 g/100 g) (Gong et al, 2018) in peanuts. Sucrose varied from 1.6 to 6.7 g/100 g. Lower values (2.6-6.5 g/100 g) were observed by Bishi (Bishi et al, 2015).…”
Section: Compositional Results Of Different Peanut Varietiessupporting
confidence: 92%
“…Based on the violin plot, most fat and protein contents of peanut varieties ranged from 49− 54 g/ 100 g and 22− 27 g/100 g, respectively. This is similar compared with previous studies for fat (48− 55 g/100 g) (Li et al, 2018) and protein (20− 26 g/100 g) (Gong et al, 2018) in peanuts. Sucrose varied from 1.6 to 6.7 g/100 g. Lower values (2.6-6.5 g/100 g) were observed by Bishi (Bishi et al, 2015).…”
Section: Compositional Results Of Different Peanut Varietiessupporting
confidence: 92%
“…Sun et al ( 2014) also detected a 0.31% decline in protein content every 10 years from 1950 to 2000 in China. In contrast, the crude protein contents for maize in the Yellow-Huai River Valley and southern China did not significantly change in our study, as reported for peanut (Li et al, 2018). This result may be because many maize breeding programs aim to improve lysine content; we found a positive correlation between crude protein content and lysine content in these two regions.…”
Section: Discussioncontrasting
confidence: 85%
“…Peanuts and soybeans are important sources of vegetable oil in China. From 1957 to 2016, the crude fat content did not change in the Yellow River region, increased in the Yangtze River region, and decreased in the southeast coast region (Li et al., 2018). From the 1940s to 2010s, soybean oil content increased in the North spring soybean region, Yellow‐Huai‐Hai summer soybean region, and south soybean region of China (Qin et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Arachis hypogaea Linn., commonly known as peanut or groundnut, is an important oil crop grown in most parts of the world [ 1 ]. Due to the characteristics of poor heat resistance and high hygroscopicity, peanuts easily go moldy under improper storage conditions.…”
Section: Introductionmentioning
confidence: 99%